Photoneutron Reaction Data for Nuclear Physics and Astrophysics - Utsunomiya Hiroaki (EPJ Web of Conferences, 2018)
We discuss the role of photoneutron reaction data in nuclear physics and astrophysics in conjunction with the Coordinated Research Project of the International Atomic Energy Agency with the code F41032 (IAEA-CRP F41032).